Life Situation of People addicted to Alcohol and Their Expectations in Terms of Help and Support based on Interviews with the so-called “Non-Alcoholics” - Przybysz-Zaremba, Małgorzata (Studia Warmińskie, 2022)
The author analyses the life situation of alcohol-dependent people. It draws attention to health, professional, material, housing and also family issues. Analyses the extent of their expectations in the area of assistance and support. The research tool used in the study was an individual in-depth (qualitative) interview, which was conducted with twenty alcohol addicts (fourteen men and six women). The subjects were aged 25-55. The interviews show that the interviewees experience many problems, disorders and dysfunctions in all indicated areas of life situations (health, work, material, housing, family) and expect specialist help and support in the process of recovery and maintaining abstinence, as well as financial support, help in finding work, improving of housing conditions (some of them even need to find housing) and rebuild proper relations with loved ones. It concludes with conclusions and recommendations for practice.